2021
DOI: 10.1002/hep4.1854
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Cell, Single‐Nucleus, and Spatial RNA Sequencing of the Human Liver Identifies Cholangiocyte and Mesenchymal Heterogeneity

Abstract: The critical functions of the human liver are coordinated through the interactions of hepatic parenchymal and non‐parenchymal cells. Recent advances in single‐cell transcriptional approaches have enabled an examination of the human liver with unprecedented resolution. However, dissociation‐related cell perturbation can limit the ability to fully capture the human liver’s parenchymal cell fraction, which limits the ability to comprehensively profile this organ. Here, we report the transcriptional landscape of 7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
188
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(203 citation statements)
references
References 42 publications
12
188
2
1
Order By: Relevance
“…Recent single cell studies unveiled the transcriptional heterogeneity of hepatocyte zones in both mouse (Halpern et al, 2017; Nault et al, 2021) and human (Aizarani et al, 2019; Payen et al, 2021) liver in high detail. Consistent with previous findings (Aizarani et al, 2019; Andrews et al, 2021; Halpern et al, 2017; Payen et al, 2021), hepatocytes in our dataset were found in a gradient between two highly distinctive states. One representing zone 1 (periportal) hepatocytes, which was characterized by high expression of genes such as Sds, Hal and Gls2, and a second representing zone 3 (pericentral) hepatocytes, which expressed Glul, Slac1a2 and Lgr5.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Recent single cell studies unveiled the transcriptional heterogeneity of hepatocyte zones in both mouse (Halpern et al, 2017; Nault et al, 2021) and human (Aizarani et al, 2019; Payen et al, 2021) liver in high detail. Consistent with previous findings (Aizarani et al, 2019; Andrews et al, 2021; Halpern et al, 2017; Payen et al, 2021), hepatocytes in our dataset were found in a gradient between two highly distinctive states. One representing zone 1 (periportal) hepatocytes, which was characterized by high expression of genes such as Sds, Hal and Gls2, and a second representing zone 3 (pericentral) hepatocytes, which expressed Glul, Slac1a2 and Lgr5.…”
Section: Resultssupporting
confidence: 93%
“…Hepatocytes constitute approximately 60% of the liver by cell number (Stanger, 2015), however due to their sensitivity to tissue dissociation, have not been well-represented in current single cell liver disease datasets. Although tissue dissociation approaches better suited to improve hepatocyte representation have been reported, they have only been applied to study healthy liver (Andrews et al, 2021; MacParland et al, 2018; Payen et al, 2021). Moreover, solid tissue dissociation for scRNA-seq introduces cell representation biases and de novo transcriptional stress responses, which may mask the underlying biological state under study (Denisenko et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We employed Harmony-based integration (19) to eliminate variations arising due to batch differences and sequencing platforms and observed clear hierarchical clustering of each cell type and representation from each patient in the individual cell clusters. Cell type annotation of Leiden clusters was based on lineage-specific markers adapted from earlier scRNA-seq studies profiling the liver (2022) (Fig. 1C and 1F), such as T cells ( CD3E, CD3D, IL7R, CD8A, CD8B, TRAC ), NK cells ( NCAM1, GNLY, NKG7, TRDC, PRF1 ), myeloid cells ( CD14, CSF1R, FCGR3A, C1QA, C1QB, IDO1, CLEC10A ), B cells ( MS4A1, MZB1, CD79A, JCHAIN ), stellate cells ( ACTA2, RGS5, COL1A1 ), endothelial cells ( PECAM1, RELN, ENG, FSCN1, CAVIN2 ), and hepatocytes ( ALB, CYP3A4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Different variants of snRNA-seq have been applied in studying various human tissue types. 58 , 59 , 60 , 61 In a recent study by Andrews et al, 62 the transcriptomic landscape of the human liver was studied by matched scRNA-seq and snRNA-seq. The use of snRNA-seq revealed the presence of rare subtypes of liver mesenchymal cells, while lymphocytes were only distinguishable by scRNA-seq.…”
Section: Discussionmentioning
confidence: 99%